Project managers' capacity-planning practices for infrastructure projects in Qatar: a multiple-case study. (29th November 2021) - Opeyemi, Ojo Emmanuel; Neubert, Michael
Infrastructure project delays and cost overrun are often caused by ineffective use of organisational skills, processes, and resources. Cost overrun and schedule delay in Qatari have had damaging effects on the national economy. The purpose of this study was to explore the perceptions of project managers regarding how they utilise capacity-planning practices to manage government-funded projects in Qatar. This study was framed by three conceptual models developed by Gill to outline capacity management needs within a construction company: the time horizon model, individual-organisation-industry levels model, and capacity development across components model. Data were collected from semistructured interviews with eight participants. Fifteen themes emerged through thematic analysis of textual data and cross-case synthesis analysis, across five conceptual categories: resources to meet performance capacity, knowledgeable and skilful staff, short- and long-term planning strategy, cost overrun issue, and time management. Findings may promote timely completion of projects, and improve the economy of Qatar.